Fuero de paternidad: tarea pendiente en la tutela de derechos laborales - Ortega Caicedo, Guillermo (2021)
The growing interest in developing guarantees for protecting labour rights, both nationally and internationally, has led different countries to include paternity license within their legal systems, some of them even contemplating the so-called paternity jurisdiction. This article aims to establish the need to guarantee safeguarding work and the consequent protection of the worker’s family nucleus, the parental jurisdiction. A study of national and comparative legislation was then carried out to verify the real scope of this jurisdiction and how it should be regulated in Ecuador, identifying the specific features that define its characteristic features in each of the countries subject to analysis. Additionally, concepts such as equality and discrimination have been developed, based on agreements adopted by the International Labour Organization. All the elements mentioned above have served as a basis to determine the weaknesses that the current national regulatory framework presents, serving for the subsequent formulation of conclusions, which show the situation of inequality and lack of protection in which the workers are and the possible strengths that would bring the inclusion of this legal figure to achieve much broader protection of the rights of the working class. KEYWORDS: social equality, legal systems, discrimination, law enforcement, labour law. JEL CODE: K, K36